2021
DOI: 10.3390/jcm10204735
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Plasma-Sprayed Titanium-Hydroxyapatite Femoral Stem in Hip Arthroplasty in Patients Older than 70 Years. Is Cementless Fixation a Reliable Option in the Elderly?

Abstract: Background: Although cementless implants are increasing in popularity, the use of cementless femoral stems for total hip arthroplasty (THA) and hip hemiarthroplasty (HH) in elderly patients remains controversial. The aim of this study was to report the outcomes of a cementless stem used in a large multicentric cohort of elderly patients receiving elective THA and HH for displaced femoral neck fracture. Methods: A total of 293 patients (301 hips) aged 70 years or older (mean age, 78 years; range, 70–93) who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Many studies have reported on outcomes of HA-coated stems [1,8,9,28,29], but only a few have reported on outcomes of other coatings. Studies on stems with first plasma-sprayed titanium and then HA coating have reported satisfactory mid-and long-term outcomes [6,[30][31][32], this coating combination may provide stronger biological and mechanical bone fixation compared to only HA coating [6,33,34]. A recent study by Liu et al [35] has shown that a pore size between 50 and 800 μm stimulates bone ingrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported on outcomes of HA-coated stems [1,8,9,28,29], but only a few have reported on outcomes of other coatings. Studies on stems with first plasma-sprayed titanium and then HA coating have reported satisfactory mid-and long-term outcomes [6,[30][31][32], this coating combination may provide stronger biological and mechanical bone fixation compared to only HA coating [6,33,34]. A recent study by Liu et al [35] has shown that a pore size between 50 and 800 μm stimulates bone ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…The design and surface coating of uncemented femoral stems for total hip arthroplasty (THA) have considerably evolved over the last 30 years to optimise osseointegration [1][2][3]. Different surface treatments and coatings have been developed to enhance bone ingrowth, including grit-blasting and sand-blasting surface treatments, as well as plasma-sprayed titanium and hydroxyapatite (HA) coatings [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness, porosity, microhardness, tensile strength, and wear resis- Similar observations were previously made by Tercero et al 268 Viswanath et al proposed the interfacial reactions in the Al 2 O 3 /HA composite. 184 When alumina is incorporated into the HA matrix, it tends to change into different forms, as described in eqn (21). The authors concluded that the diffusion of Ca 2+ ions from HA into the alumina matrix leads to TCP and other secondary phases of HA.…”
Section: Ceramic-reinforced Ha Composite Coatingsmentioning
confidence: 99%
“…8 Implant surfaces modified by hydroxyapatite (HA) are extensively employed in revision surgeries, especially in the femoral stem of the hip implant revision surgeries. [19][20][21] HA is one of the potential candidates that mimic the properties of bone.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a meta-analysis by Chen et al showed that although the survival rate of hydroxyapatite coating is similar to porous coating, the femoral osteolysis is greater in the porous group [17]. Cementless plasma-sprayed porous titanium hydroxyapatite stems have a 98.5% survivorship in patients aged 70 or older for femoral neck fractures, on a study performed on 293 patients (301 hips) [18].…”
Section: Surface Treatmentmentioning
confidence: 99%